SPEAKING DALAM PRAKTIK KOMUNIKASI DIGITAL PEMERINTAH: ANALISIS MAKNA SOSIAL REELS INSTAGRAM BKPP KOTA SEMARANG - Agus Edy Laksono; RR. B. Natalia Sari Pujiastuti; Suhariyanto; Viro Dharma Saputra (Fakultas Bahasa dan Sastra Universitas PGRI Kanjuruhan Malang, 2026)
The development of digital technology has brought significant changes to governmental communication practices, particularly in the ways public institutions disseminate information, construct institutional images, and establish relationships with the public. In this context, the Regional Personnel, Education, and Training Agency (Badan Kepegawaian, Pendidikan, dan Pelatihan—BKPP) of Semarang City utilizes social media, especially video-based content, as a primary channel for public communication. This study aims to examine the communication practices of BKPP Semarang City on social media from the perspective of the ethnography of communication by applying the SPEAKING analytical framework proposed by Dell Hymes. Employing a qualitative approach, this study analyzes BKPP’s video uploads as speech events that are embedded within specific social, cultural, and institutional contexts. The findings reveal that the elements of setting, participants, and ends consistently represent bureaucratic communication oriented toward policy dissemination, institutional image-building, and the reinforcement of the role of civil servants in public service. Socially, these communication practices produce meanings related to the ideal identity of civil servants as professional, ethical, and responsible actors, while simultaneously constructing a symbolic relationship between the government and the public framed by proximity, openness, and policy legitimacy in the digital era.